2021
DOI: 10.1177/10783903211066125
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Satisfaction, Burnout, and Secondary Traumatic Stress Among Nursing Staff at an Academic Medical Center: A Cross-Sectional Analysis

Abstract: Background: Although several studies have recently described compassion satisfaction (CS), burnout (BO), and secondary traumatic stress (STS) in nurses, few to date have examined these issues across nursing specialties. Such examination is needed to inform future nursing-subspecialty tailored interventions. Aims: To examine (1) differences in CS, BO, and STS across nursing specialties and (2) differences associated with demographic, work-related, and behavioral factors among nurses. Method: A secondary analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Some studies suggest that having experienced adversity in the past may predispose individuals toward compassion ( Lim and DeSteno, 2016 ). Nurses’ BO and STS risk factors should be assessed and specialty-specific interventions may be considered to improve CS while reducing BO and STS among nurses ( Lykins et al, 2021 ). Nursing managers should implement practical and comprehensive plans to increase nurses’ CS and reduce BO and STS ( Zakeri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that having experienced adversity in the past may predispose individuals toward compassion ( Lim and DeSteno, 2016 ). Nurses’ BO and STS risk factors should be assessed and specialty-specific interventions may be considered to improve CS while reducing BO and STS among nurses ( Lykins et al, 2021 ). Nursing managers should implement practical and comprehensive plans to increase nurses’ CS and reduce BO and STS ( Zakeri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses have certainly done their part in advancing the professional journey, enhancing patient outcomes, social relevance, and professional equity. Yet, in the confines of hospitals and health services, the largest employers of nurses, many nurses still feel so personally and professionally disenfranchised that they suffer more than any other group of professional women from depression, anxiety, obesity, dissatisfaction, burnout, and marital failure (Chong & Shorey, 2022;Jarden et al, 2021;Lykins et al, 2021).…”
Section: Nursing Progressmentioning
confidence: 99%
“…While these experiences and sentiments were real to most nurses, what was most often expressed were devastated feelings of loss. [5][6][7] These feelings were most often expressed in terms that indicated a generalized sense of loss of support, engagement, investment, leadership, and empowerment. Indeed, many nurses who left either the organization or the profession indicated that they expected the pressures and stressors associated with the accelerating care demands of COVID but did not expect the organizational and leadership shortfalls they often strongly experienced in the midst of the pressures of COVID response.…”
Section: Introductionmentioning
confidence: 99%